Осокові Львівщини: біорозмаїтість і охорона - Данилик, І. (Праці наукового товариства ім. Шевченка, 2001)
Наведені результати критико-таксономічного, хорологічного та природоохоронного дослідження видів рослин родини Cyperaceae Juss. флори Львівської области. Конспект системи родини Cyperaceae флори Львівщини відображає її систематичну структуру до підвидового рангу включно. Виявлені рідкісні та зникаючі види в межах адміністративних районів, серед яких 6 видів занесені до „Червоної книги України”. The results of critic-taxonomical and chorological study of one of the largest (by the species number) Cyperaceae Juss. family of the flora of the Lviv region are presented. Taxonomical composition of the studied family is elucidate. It consists of 91 species from 12 genera (61,9% of specific and 63,2% of generic diversity of the Cyperaceae family of Ukraine). Previously noticed 11 species have been removed from the check-list as a result of the study. The systematic structure including subspecific level is presented in the summary of the Cyperaceae family in Lviv region database. The dispersal of 29 rare and declining species (6 of which are included into the Ukrainian Red Data Book, 1996) has been analysed for the districts of the Lviv region. Detailed information is given for the distribution of nine species reported from single localities. The proposals to improve the conservation status for the Cyperaceae family species of the Lviv region are presented.